Automated Measurement System for Room Acoustics – an Initial Feasibility Study - BORKOWSKI, Bartłomiej Dariusz; PLUTA, Marek (Archives of Acoustics, 2015)
Currently used procedures in room acoustics measurements are not automated. Particularly in medium-sized and large areas they require a lot of time and intensive labour which directly translates into an increase in the measurement cost. Introduction of an automated system would increase efficiency of the measurements, and therefore could present both practical and scientific benefit. The paper presents initial feasibility study for designing a system that permits the measurement of selected acoustic parameters for any choice of three-dimensional grid of measurement points throughout the volume of the room. The system will utilize an autonomous probe attached to a blimp, and will be able to measure and analyze acoustic characteristics of the rooms. The article discusses the initial choices of the system elements, starting from the general idea, through the mechanical design and control procedures, the software that controls positioning and flying of the probe, up to the automation of the measurement procedure and its possible impact on the acoustic field.